Strategi Tokoh Agama dan Pemerintah Desa dalam Meningkatkan Efektivitas Jamaah Sholat Subuh di Desa Pajar Bulan Kecamatan Seginim: Penelitian - Sunia Junida; Boby Hendro Wardono; Dikalni; Yela Karima Jeni Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to identify the strategies implemented by religious leaders and the village government in improving the effectiveness of Subuh congregational prayer, as well as to examine the obstacles they encountered. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observations, and documentation, with triangulation techniques used to ensure data validity. The findings revealed that the strategies included communicative preaching approaches, exemplary behavior by religious leaders, support through adequate mosque facilities, and active collaboration between religious leaders and the village government in organizing religious programs. However, these efforts faced several obstacles, both internal such as low awareness and irregular sleeping patterns among youth and external, including weather conditions and the distance between homes and the mosque. The study concluded that the collaborative role of religious leaders and the village government was crucial in fostering collective awareness and encouraging increased youth participation in Subuh congregational prayer.